2021
DOI: 10.3389/fpsyt.2021.778992
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone-Smartcard Platform for Implementing Contingency Management in Buprenorphine Maintenance Patients With Concurrent Stimulant Use Disorder

Abstract: Background and Objectives: Opioid agonist pharmacotherapies are effective in the treatment of opioid use disorder (OUD) but concurrent stimulant use is common and can lead to relapse and treatment drop out. Contingency management in combination with opioid agonist pharmacotherapy has broad beneficial effects in polysubstance users, including promoting drug abstinence and treatment retention, but clinic-based implementation can be burdensome. The present study was conducted to evaluate a contingency management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Differences between groups increased over time, and by the final timepoint, the odds ratio for the drug abstinence measure was 4.84. A similar study involving the same intervention showed similar results in a sample of patients receiving medications for opioid use disorder (i.e., buprenorphine) who had concurrent stimulant use disorder (DeFulio et al, 2021a).…”
Section: Technology To Promote Access To High-fidelity CMmentioning
confidence: 75%
“…Differences between groups increased over time, and by the final timepoint, the odds ratio for the drug abstinence measure was 4.84. A similar study involving the same intervention showed similar results in a sample of patients receiving medications for opioid use disorder (i.e., buprenorphine) who had concurrent stimulant use disorder (DeFulio et al, 2021a).…”
Section: Technology To Promote Access To High-fidelity CMmentioning
confidence: 75%
“…While the use of technology-based CM has been growing (Dallery et al, 2019) the present study was a novel integration of a smartphone-based CM program into a usual care setting. The same technology has effectively promoted clinic appointment attendance and drug abstinence in an inner-city outpatient clinic (DeFulio, Furgeson, et al, 2021; DeFulio, Rzeszutek, et al, 2021). Taken together, these studies demonstrate the role of smartphone-based CM to promote entry and adherence to MAT.…”
Section: Resultsmentioning
confidence: 99%
“…Incentives are delivered via an anonymous credit card that cannot be used to withdraw cash and has additional purchasing protections. Studies show preliminary effectiveness of this model in patients with OUD, including one with patients who have concurrent StUD 89-91 …”
Section: Behavioral Treatmentmentioning
confidence: 96%
“…Studies show preliminary effectiveness of this model in patients with OUD, including one with patients who have concurrent StUD. [89][90][91] The CGC reviewed available evidence for a number of technology-based and alternative interventions but found it to be insufficient to include in the recommendation statements at this time. These items can be found in Appendix F, http://links.…”
Section: Technology-based Interventionsmentioning
confidence: 99%